2013
DOI: 10.1007/s13404-013-0087-8
|View full text |Cite
|
Sign up to set email alerts
|

Extended reliability of gold and copper ball bonds in microelectronic packaging

Abstract: Wire bonding is the predominant mode of interconnection in microelectronic packaging. Gold wire bonding has been refined again and again to retain control of interconnect technology due to its ease of workability and years of reliability data. Copper (Cu) wire bonding is well known for its advantages such as cost-effectiveness and better electrical conductivity in microelectronic packaging. However, extended reliabilities of Cu wire bonding are still unknown as of now. Extended reliabilities of Au and Pd-coate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 20 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…Figure 13 illustrates a Cu ball bond with lower package reliability margin and usually more susceptible to Cu moisture corrosion test under UHAST condition. This has been reported in our previous literature works [8,[25][26][27]31]. Cu ball bond has a layer of Pd coated on low-corrosive resistance Cu wire which inhibits moisture ball bond corrosion in UHAST conditions (130°C, 85 %RH).…”
Section: Cu and Au Ball Bond Corrosion (Biased Hast And Unbiased Hast)supporting
confidence: 65%
See 1 more Smart Citation
“…Figure 13 illustrates a Cu ball bond with lower package reliability margin and usually more susceptible to Cu moisture corrosion test under UHAST condition. This has been reported in our previous literature works [8,[25][26][27]31]. Cu ball bond has a layer of Pd coated on low-corrosive resistance Cu wire which inhibits moisture ball bond corrosion in UHAST conditions (130°C, 85 %RH).…”
Section: Cu and Au Ball Bond Corrosion (Biased Hast And Unbiased Hast)supporting
confidence: 65%
“…Pd atoms in the Pd-coated Cu wire do not participate in the interfacial reaction, and have no marked effect on the growth rate of IMCs. Gan et al conducted studies on effects of bonding wires on UHAST and TC reliability and found Au with better UHAST reliability compare to Cu wire [25][26][27][28][29][30][31]. Au ball bond is well known with its Au atomic diffusion into Al metallization and caused resistive ball bonds with non-optimized bonding parameter [1,25].…”
Section: Introductionmentioning
confidence: 99%
“…Moisture-induced corrosion at the Ag/Al bonding interface seems to be the root cause of this failure. Similar corrosion effect is also observed in Au-Al and Cu-Al wire-bonds [20][21][22][23]. The corrosion is strongly associated with halogen content, such as chlorine (Cl), in the epoxy molding compounds (EMCs).…”
mentioning
confidence: 65%
“…While Al wire has the critical distinction with Au wire that the surface does not need to be heated, which make it suitable for temperature sensitive surfaces [11]. Gan et al [1,12] discussed the influence of wire materials on the bonding reliability, which found that the Au wire remained connecting for a longer time before failure than other materials even though with the disadvantage of expensive. Murali et al [13] aimed at the varying wire size and thermal aging periods, investigating the interface morphology and metallurgical behavior of the Au wire bonding area.…”
Section: Introductionmentioning
confidence: 99%